2019
DOI: 10.1073/pnas.1809855116
|View full text |Cite
|
Sign up to set email alerts
|

Musical reward prediction errors engage the nucleus accumbens and motivate learning

Abstract: Enjoying music reliably ranks among life’s greatest pleasures. Like many hedonic experiences, it engages several reward-related brain areas, with activity in the nucleus accumbens (NAc) most consistently reflecting the listener’s subjective response. Converging evidence suggests that this activity arises from musical “reward prediction errors” (RPEs) that signal the difference between expected and perceived musical events, but this hypothesis has not been directly tested. In the present fMRI experiment, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 46 publications
(99 reference statements)
1
105
0
6
Order By: Relevance
“…In the domain of music, Gold et al . showed that musical stimuli, specifically chords and chord progressions with consonant or dissonant endings, can generate rewards and reward prediction errors that motivate learning in a reinforcement‐learning protocol . This result shows that because of the systematic relationship between consonance and pleasure at least in most westernized listeners, music itself—specifically, consonant chord endings to chord progressions—can function both as a prediction (in this case, the chord progression) and a reward (in this case, consonant endings as opposed to dissonant endings).…”
Section: What Is the Nature Of The Interaction Between Auditory To Rementioning
confidence: 97%
See 2 more Smart Citations
“…In the domain of music, Gold et al . showed that musical stimuli, specifically chords and chord progressions with consonant or dissonant endings, can generate rewards and reward prediction errors that motivate learning in a reinforcement‐learning protocol . This result shows that because of the systematic relationship between consonance and pleasure at least in most westernized listeners, music itself—specifically, consonant chord endings to chord progressions—can function both as a prediction (in this case, the chord progression) and a reward (in this case, consonant endings as opposed to dissonant endings).…”
Section: What Is the Nature Of The Interaction Between Auditory To Rementioning
confidence: 97%
“…While this work indicates that pleasurable music engages similar brain structures to other rewarding experiences, more recent work has investigated the idea that music itself can serve as a reward. One recent fMRI study investigated the neural responses to music in a reward‐learning context . Taking an established reward prediction error task and substituting music (where consonant music is assumed as a reward, and dissonant music is punishment), the authors identified that the NAcc responded to reward prediction errors in music.…”
Section: Roles Of the Auditory And Reward Systems In Musical Pleasurementioning
confidence: 99%
See 1 more Smart Citation
“…Reward signals are intimately linked with the activity of dopamine neurons in regions of the brainstem such as the ventral tegmental area (VTA), as well as targets of those neurons, particularly the nucleus accumbens (NAcc). Classically, the VTA 43,44 and NAcc 12,45,46 respond strongly when rewards are larger or earlier than expected (i.e., reward prediction errors, or RPEs). However, the VTA can respond more broadly to variables other than reward 47 , including sensory PEs 48-50 , unexpected events 51,52 , aversive PEs 53 , changes in hidden belief states 31,54 , reward expectation 55,56 , advance information 57 , and stimulusstimulus learning 58 , all in the absence of (or controlling for) reward.…”
Section: Surprise Correlates With Enjoyment and Neural Activity In Rementioning
confidence: 99%
“…Surprise is theorized to be critical for learning and memory 6,7 , updating our beliefs about the structure of the world 8 , and demarcating events in the continuous flow of time 9 . Moreover, although people typically prefer certainty about outcomes that are instrumental for survival 10 , in domains with noninstrumental information, such as narratives, music, and sports, people tend to prefer violations of their expectations [11][12][13] , suggesting that surprise is often a rewarding affective experience.…”
Section: Introductionmentioning
confidence: 99%